Carbon Management Accounting, Profitability, and Carbon Tax Intensity: The Moderating Role of the Energy Mix - Adinda Dwika Rahma; W. Widyasari (Golden Ratio of Auditing Research, 2027)
The energy sector is the largest contributor to greenhouse gas emissions in Indonesia and is the first sector subject to the carbon tax under Law No. 7 of 2021 on the Harmonization of Tax Regulations. This study investigates the effect of Carbon Management Accounting (CMA) on profitability and carbon tax intensity, while examining the moderating role of the energy mix, measured by the consumption ratios of coal, diesel, and biodiesel. Unlike previous studies that proxy CMA using disclosure indices or PROPER ratings, this study measures CMA directly based on the quantification of Scope 1 carbon footprint using emission factors from the Intergovernmental Panel on Climate Change (IPCC) Tier 1 and Indonesia's Ministry of Energy and Mineral Resources (MEMR) Tier 2. The sample consists of six coal mining companies listed on the Indonesia Stock Exchange during the 2020–2024 period, yielding 30 firm-year observations selected through purposive sampling. The data were analyzed using Moderated Regression Analysis (MRA) based on a Fixed Effects Model with White cross-section robust standard errors in EViews 13. The results indicate that CMA has no significant effect on profitability, measured by Return on Equity (ROE), across all models (p = 0.8133, 0.3268, and 0.4930), and none of the three energy mix ratios moderates this relationship. In contrast, CMA has a significant positive effect on carbon tax intensity in both the diesel model (β = 0.00138, p = 0.0026) and the biodiesel model (β = 0.00348, p = 0.0020). Furthermore, all three energy mix ratios significantly moderate this relationship. The coal consumption ratio strengthens the positive effect of CMA on carbon tax intensity (β = 0.00567, p = 0.0028), whereas the diesel (β = −0.00216, p = 0.0186) and biodiesel (β = −0.00348, p = 0.0059) consumption ratios weaken it. These findings suggest that the benefits of CMA are more evident in reducing carbon tax exposure than in improving firms' short-term profitability.